Determination of ecological flow thresholds for rainfall-recharging rivers based on multiple hydrological methods - Yu, Jiandong; Yu, Shouchao; Zhang, Hengjia; Wang, Zeyi; Zhou, Chenli; Chen, Xietian (Frontiers in Environmental Science, 2023)
Given the threats to the regional river ecological flow, including the sharp increase in per capita water demand, the increase in the number of hydraulic engineering, and the strong seasonal runoff of rainfall recharge channels, we clarified the appropriate ecological flow thresholds for the middle reaches of Bailong River of northwest China. Based on the monthly runoff data in the Wudu Hydrological Station of Bailong River from 1990 to 2020, seven suitable hydrological methods were used to couple the estimation of the ecological flow in the middle reaches of Bailong River, which were tested by runoff satisfaction level analysis, using quadratic fit and 95% confidence interval to determine the monthly ecological flow and threshold of the river in the study area. The results by using the single hydrological methods showed that the calculation results from the monthly minimum ecological runoff calculation method, the improved RVA method, the Tennant method, and the DC method were four better estimation methods, which had a satisfaction level of more than 90% in the whole year. The improved RVA method and the Tennant method were more suitable for the diversion power station whose main task aimed at power generation. The calculation results from the improved RVA method were tested and analyzed by the Tennant method, which were extremely poor from November to April in the following year, and could not meet the minimum ecological water requirements for the biological community in the river channel. While the other five methods all meet this requirement. We suggest that the minimum ecological flow in the middle reaches of the Bailong River maintained at 27.28 m3⁄s, and the maximum retained at 116.33 m3⁄s. The calculation results were in line with the dynamics of runoff in the study area, which could improve the accuracy of water ecological protection. The calculation results of this study could be used for the middle reaches of the Bailong River and may provide a reference for follow-up ecological restoration research and management in similar ecological zones.